2018
DOI: 10.1080/10962247.2017.1407837
|View full text |Cite
|
Sign up to set email alerts
|

Personal exposure to fine particulate matter concentrations in central business district of a tropical coastal city

Abstract: Personal exposure monitoring at an urban hotspot indicated space and time variation in PM concentrations that is not captured by the fixed air quality monitoring networks. The short-term exposure to higher concentrations can have a significant impact on health that need to be considered for the health risk-based air quality management. The study emphasizes the need of hotspot-based monitoring complementing the already existing fixed air quality monitoring in urban areas. The personal exposure patterns at hotsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Similar to other studies (e.g. [24,26,[31][32][33]), we found that exposure levels varied among the selected occupations and even within occupation depending on nature, time, duration and location of work. Average PM 2.5 exposure was relatively higher in rickshaw drivers and street vendors with average eight hours of exposure value of 68±27.9 μg m −3 and 66.6±33.9 μg m −3 respectively.…”
Section: Exposure To Ambient Air Pollution By Occupationsupporting
confidence: 90%
“…Similar to other studies (e.g. [24,26,[31][32][33]), we found that exposure levels varied among the selected occupations and even within occupation depending on nature, time, duration and location of work. Average PM 2.5 exposure was relatively higher in rickshaw drivers and street vendors with average eight hours of exposure value of 68±27.9 μg m −3 and 66.6±33.9 μg m −3 respectively.…”
Section: Exposure To Ambient Air Pollution By Occupationsupporting
confidence: 90%
“…Researchers have employed monitored data (fixed monitors, mobile monitors and sensors) (Kumar et al, 2015;Menon and Nagendra, 2018), satellite data (Chitranshi et al, 2015;Mahapatra et al, 2019), modeling and combined approaches (Xie et al, 2017;Mandal et al, 2020) to identify air pollution hotpots within the cities.…”
Section: Air Pollution Exposure In Urban Areasmentioning
confidence: 99%
“…At industrial and high traffic areas, it changes spatially within meters and over time within hours. For example, Menon et al, reported a change in particulate concentration at high business streets during the morning, afternoon and evening for a tropical coastal city in India [ 14 ]. Citizen science applications such as personal exposure monitoring and occupational exposure monitoring need high spatial and temporal resolutions [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%